INCREASED BIOMEDICAL POTENTIAL OF Pleurotus ostreatus THROUGH THE USAGE OF EFFECTIVE SUBSTRATE - S.DATTA; S.SHYAM CHOUDHURI; A.K.MITRA (International Journal of Pharma and Bio Sciences, 2014)
Mushrooms have been used as food supplement from times immemorial not only for their nutritive value, but also for their medicinal properties. This investigation attempts to update the present cultivation status and project the future prospects of the oyster mushroom, Pleurotus ostreaus for its biomedical potential. Comparative analysis of the yield and the chemical composition of clusters of Pleurotus ostreatus were performed by cultivating them on three different substrates, viz, paddy straw, wheat straw and sugarcane waste (bagasses). Thereafter extrapolating the results to compare their biomedical potential by means of various spectrophotometric assays. The genetic variation among the clusters was studied using RAPD markers, OPAB18, OPAC19, OPAC13 by Polymerase Chain Reaction (PCR) and dendrogram analysis. The yield of Pleurotus ostreatus was seen to be comparable in case of paddy and wheat straw while for sugarcane waste it was almost 50% lower. Results correlated with the substrate degrading enzymes, enzymatic and non-enzymatic antioxidants and bioactive compounds.